Narcissus and Goldmund - Hesse, Hermann, 1877-1962 (Picador, 2003)
Leaving behind the medieval monastary of Mariabronn at the urgings of his instructor, Narcissus, Goldmund embarks on a fantastic journey to recapture his past and discover his future.